Romance in the Workplace: Analysis of Justice Perception toward Policies Concerning Romance in the Workplace - Muhammad Irfan Syaebani; Riani Rachmawati (Universitas Airlangga, 2017)
Romance in the workplace is a common phenomenon and inevitable from organization dynamics. Romance in the workplace has double effects to the organization: positive and negative. Therefore, organization must be careful in formulating policies concerning this phenomenon. Literature said that in formulation policies concerning romance in the workplace it must be started from organizational justice theory. This research tries to find out what policies which perceived as the most fair. Quasi experiment method with scenario instrument is chosen. This method allows experiment subjects to give response to different combinations/varieties of romance in the workplace based on 4 criterias (type of romance – origin of couple – impact of romance – romance policies). Subject of experiment is master students of management study program in Universitas Indonesia who has working experiences as condition for participating and 30 students agreed to partake in experiment. Result shows that giving counseling is perceived as the most fair policy for all combinations/varieties of romance in the workplace. It shows that organization’s response to romance in the workplace should not coercive policies.